Vaccine Development Against Leishmania donovani - Das, Amrita; ALI, NAHID (Frontiers in Immunology, 2012)
Visceral leishmaniasis (VL) caused by Leishmania donovani and Leishmania infantum/chagasi represents the second most challenging infectious disease worldwide, leading to nearly 500,000 new cases and 60,000 deaths annually. Zoonotic VL caused by L. infantum is a re-emergent canid zoonoses which represents a complex epidemiological cycle in the New world where domestic dogs serve as a reservoir host responsible for potentially fatal human infection and where dog culling is the only measure for reservoir control. Life-long immunity to VL has motivated development of prophylactic vaccines against the disease but very few have progressed beyond the experimental stage. No licensed vaccine is available till date against any form of leishmaniasis. High toxicity and increasing resistance to the current chemotherapeutic regimens have further complicated the situation in VL endemic regions of the world. Advances in vaccinology, including recombinant proteins, novel antigen-delivery systems/adjuvants, heterologous prime-boost regimens and strategies for intracellular antigen presentation, have contributed to recent advances in vaccine development against VL. Attempts to develop an effective vaccine for use in domestic dogs in areas of canine VL should be pursued for preventing human infection. Studies in animal models and human patients have revealed the pathogenic mechanisms of disease progression and features of protective immunity. This review will summarize the accumulated knowledge of pathogenesis, immune response, and prerequisites for protective immunity against human VL. Authors will discuss promising vaccine candidates, their developmental status and future prospects in a quest for rational vaccine development against the disease. In addition, several challenges such as safety issues, renewed and coordinated commitment to basic research, preclinical studies and trial design will be addressed to overcome the problems faced in developing prophylactic strategies for protection against this lethal infection.